1997
DOI: 10.1105/tpc.9.10.1757
|View full text |Cite
|
Sign up to set email alerts
|

Hypervariable Domains of Self-Incompatibility RNases Mediate Allele-Specific Pollen Recognition.

Abstract: 'Self-incompatibility (SI) in angiosperms is a genetic mechanism that promotes outcrossing through rejection of selfpollen. In the Solanaceae, SI is determined by a multiallelic S locus whose only known product is an S RNase. S RNases show a characteristic pattern of five conserved and two hypervariable regions. These are thought to be involved in the catalytic function and in allelic specificity, respectively. When the Solanum chacoense Si&, genotype is transformed with an Sll RNase, the styles of plants expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(70 citation statements)
references
References 38 publications
2
68
0
Order By: Relevance
“…The results showed that the non-glycosylated S 3 -RNase retained the full ability to reject self-pollen, suggesting that the recognition function of S-RNase resides in its amino-acid sequence . Domain-swapping experiments were performed to examine the role of the two hypervariable domains in allelic specifi city (Kao and McCubbin 1996 ;Matton et al 1997 ;Zurek et al 1997 ;Matton et al 1999 ). Swapping HVa and HVb between S 11 -RNase and S 13 -RNase of Solanum chacoense (which differ by four amino acids in the hypervariable regions) was suffi cient to switch the allelic specifi city (Matton et al 1997(Matton et al , 1999.…”
Section: Identifi Cation and Characterization Of The S-rnase Genementioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the non-glycosylated S 3 -RNase retained the full ability to reject self-pollen, suggesting that the recognition function of S-RNase resides in its amino-acid sequence . Domain-swapping experiments were performed to examine the role of the two hypervariable domains in allelic specifi city (Kao and McCubbin 1996 ;Matton et al 1997 ;Zurek et al 1997 ;Matton et al 1999 ). Swapping HVa and HVb between S 11 -RNase and S 13 -RNase of Solanum chacoense (which differ by four amino acids in the hypervariable regions) was suffi cient to switch the allelic specifi city (Matton et al 1997(Matton et al , 1999.…”
Section: Identifi Cation and Characterization Of The S-rnase Genementioning
confidence: 99%
“…Domain-swapping experiments were performed to examine the role of the two hypervariable domains in allelic specifi city (Kao and McCubbin 1996 ;Matton et al 1997 ;Zurek et al 1997 ;Matton et al 1999 ). Swapping HVa and HVb between S 11 -RNase and S 13 -RNase of Solanum chacoense (which differ by four amino acids in the hypervariable regions) was suffi cient to switch the allelic specifi city (Matton et al 1997(Matton et al , 1999. However, in the case of P. infl ata and N. alata S-RNases examined, the two hypervariable regions are necessary but not suffi cient for allele specifi city.…”
mentioning
confidence: 99%
“…Matton et al [49] investigated the role of the HV regions in allelic specificity using another Solanaceous species, Solanum chacoense. This study differed from those described above in that the S-RNases used, the S 11 -and S 13 -RNases, are almost identical, with only ten different amino acids.…”
Section: Determinants Of S-rnase Allele Specificitymentioning
confidence: 99%
“…Three of these amino acids are localized to the HVa region and one to the HVb region [50]. Using site-directed mutagenesis, Matton et al [49] substituted all four amino acids in the HV regions of an S 11 -RNase with those of an S 13 -RNase. Transgenic S 12 S 14 S. chacoense plants expressing the chimeric S 11 -RNase successfully rejected S 13 pollen but not S 11 pollen, therefore suggesting that the HVa and HVb regions together are sufficient to control S allele specificity [49].…”
Section: Determinants Of S-rnase Allele Specificitymentioning
confidence: 99%
See 1 more Smart Citation